Isothermal kinetics of diesel soot oxidation over La0.7K0.3ZnOy catalysts - Prasad R.; Kumar A.; Mishra A. (My University, 2025)
This paper describes the kinetics of catalytic oxidation of diesel soot with air under isothermal condi-tions (320-350 °C). Isothermal kinetics data were collected in a mini-semi-batch reactor. Experiments were performed over the best selected catalyst composition La0.7K0.3ZnOy prepared by sol-gel method. Characterization of the catalyst by XRD and FTIR confirmed that La1-xKxZnOy did not exhibit perovskite phase but formed mixed metal oxides. 110 mg of the catalyst-soot mixture in tight contact (10:1 ratio) was taken in order to determine the kinetic model, activation energy and Arrhenius con-stant of the oxidation reaction under the high air flow rate assuming pseudo first order reaction. The activation energy and Arrhenius constant were found to be 138 kJ/mol and 6.46×1010 min-1, respec-tively. © 2014 BCREC UNDIP. All rights reserved.